A succinct review and analysis of drivers and impacts of agricultural land transformations in Asia. (March 2021) - Prabhakar, S.V.R.K.
Highlights: The analysis indicated a positive correlation between socioeconomic factors and agricultural land change in Asia. A negative correlation between agricultural land and urban population signified agricultural land decline in Asia. Higher agricultural productivity gains contributed to the farm land decline in some countries in Asia. An increase in the agricultural area has not addressed the higher food import dependency in several countries in Asia. Abstract: This paper identifies major transformations in agricultural land both in terms of land use and land-use changes, analyses major drivers and impacts, and describes the major policy interventions to arrest negative trends. The rapidly growing population and their needs constitute one of the major drivers of land-use changes in the Asia region. Agricultural productivity has increased at a slightly faster pace than population growth in Asia through agricultural intensification. Intensive farming practices have put pressure on ecosystems leading to declining total factor productivity, land degradation, soil erosion, loss of soil fertility, and GHG emissions. Policy measures to address unsustainable land transformations have been minimal and countries are yet to be successful in arresting the negative trends. Through coordinated land management and integrated land decision support systems, countries can address food-fuel conflicts, arrest negative environmental consequences, enhance rural prosperity, and achieve sustainable development.